Controllable Syntheses of Porous Metal–Organic Frameworks: Encapsulation of LnIII Cations for Tunable Luminescence and Small Drug Molecules for Efficient Delivery. Issue 43 (11th September 2013) - Wang, Yun; Yang, Jin; Liu, Ying‐Ying; Ma, Jian‐Fang
Abstract Two porous metal–organic frameworks (MOFs), [Zn3(L)(H2O)2]⋅3 DMF⋅7 H2O (MOF‐1) and [(CH3)2NH2]6[Ni3(L)2(H2O)6]⋅3 DMF⋅15 H2O (MOF‐2), were synthesized solvothermally (H6L=1, 2, 3, 4, 5, 6‐hexakis(3‐carboxyphenyloxymethylene)benzene). In MOF‐1, neighboring ZnII trimers are linked by the backbones of L ligands to form a fascinating 3D six‐connected framework with the point symbol (412.63) (412.63). In MOF‐2, eight L ligands bridge six NiII atoms to generate a rhombic‐dodecahedral [Ni6L8] cage. Each cage is surrounded by eight adjacent ones through sharing of carboxylate groups to yield an unusual 3D porous framework. Encapsulation of LnIII cations for tunable luminescence and small drug molecules for efficient delivery were investigated in detail for MOF‐1.